Partograph pocketbook application specifically for midwifery students in filling out partographs - Setiawati, Iin; Nikmah, Nurun (International Journal of Health Science and Technology, 2023)
One of the objectives of the Health Education (midwifery) curriculum is to make midwives professionals in the early detection of maternal and neonatal emergencies. Compulsory courses that teach early detection are obstetric care for childbirth and newborns, namely early detection using a partograph. The results of preliminary studies in midwifery 3rd-semester students can be six (60%) filling in the partograph incorrectly and incompletely and four (40%) filling in the partograph correctly and completely. This study aims to analyze the effectiveness of applying partograph pocketbooks by students to fill out partographs. The research design used in the study was pre-experimental with the one-group pretest-posttest design approach. Partograph filling dependent variable and independent variable: partograph pocketbook. Has passed the ethical test with certificate number 1576/KEPK/STIKES-NHM/EC/1/20203. The statistical test used paired T-test with Î± 0.05. The results of the study of filling in the partograph of midwifery students before using the partograph pocketbook had a value of almost half 62-71, while the results of filling in the partograph of midwifery students after using the partograph pocketbook were mostly 82-91, statistical tests showed 0.00< 0.05 which means that the partograph pocket book effectively helps students in filling out the partograph. This research can be a source of knowledge for students to improve their skills in filling partographs.